Nutritional status, swallowing disorders, and respiratory prognosis in adult Duchenne muscular dystrophy patients. Issue 7 (3rd May 2021) - Fayssoil, Abdallah; Chaffaut, Cendrine; Prigent, Helene; Laforet, Pascal; Clair, Bernard; Orlikowski, David; Ogna, Adam; Chevret, Sylvie; Meng, Paris; Annane, Djillali; Lofaso, Frederic; Crenn, Pascal
Abstract: Malnutrition and swallowing disorders are common in Duchenne muscular dystrophy (DMD) patients. We assessed, in adult DMD with home mechanical ventilation (HMV) and cough assist device, its prevalence and the relationships with respiratory muscle strength and long‐term respiratory prognosis. We reviewed the patients ( n = 117, age 18–39 years [median 24]), followed in a reference center, from 2006 to 2015, to obtain clinical baseline, nutritional status, vital capacity (VC), maximal inspiratory pressure (MIP), and maximal expiratory pressure (MEP). The median body mass index (BMI) was low (15.6 kg/m²). Included patients had severe restrictive respiratory function with a median VC of 10.5% [7–17] of the predicted value. All patients were on HMV. Prevalence of malnutrition, swallowing disorders, and gastrostomy were respectively 62%, 34%, and 11%. BMI and serum albumin level were significantly associated with MIP, MEP, and VC. The 1‐year/5‐years cumulative incidences of respiratory events (pulmonary sepsis and acute respiratory distress) were, respectively, 20.7%/44.5%. Using univariate analysis, predictive factors for respiratory events were swallowing disorders ( p = .001), transthyretinemia ( p = .034), MIP ( p = .039), and MEP ( p = .03) but not BMI or albuminemia. Using multivariate analysis, only swallowing disorders remained significantly associated with respiratory events (OR = 4.2, IC 95% 1.31–12.2, p = .01). In conclusion, this study highlights the interrelationships between nutritional intake, swallowing function, airway clearance, and respiratory function in adult DMD. A multidisciplinary approach focusing on these previous factors is essential to optimize DMD patient health.